Geologi Teknik dan Analisis Kestabilan Lereng pada Daerah Perkantoran Tirawuta, Kabupaten Kolaka Timur, Sulawesi Tenggara (Jurnal Geomine, 2023)
Engineering geological mapping and slope stability analysis have been conducted in Tirawuta Area, East Kolaka Regency, Southeast Sulawesi. This research aims to present the geological conditions of the office area, including geomorphological units, lithological types of slope, and the physical and mechanical properties of slope materials. The research area comprises silt sand units (SP-ML), clay sand units (SP-CL), and schist units. The schist has a low compressive strength (6.63 MPa) due to the high weathering degrees. The unit weight of the lithologies that make up the slope is 13.52 kN/m³-16.26 kN/m³ with a medium plasticity index (6.88-14.33). Determination of the slope factor of safety was carried out using the Bishop Method in two sections. The analysis showed that slope A was stable, while slope B had a factor of safety (FoS) close to the threshold value (FoS=1.27). Sensitivity analysis on the unit weight and shear strength parameters showed that silty and clay sand units control slope stability. Changes in the cohesion and friction angle in the clay sand unit affect the factor of safety on Slope A and the silty sand unit on Slope B. Cohesion and friction angle at critical slope conditions are positively correlated based on the regression curve. Geometry optimization on Slope B is recommended by changing the slope geometry by reducing the slope angle and creating benches.